Germination study of seeds of some species of the Zygophyllaceae B.R. family under different environmental and laboratory conditions in Basra Governorate. - محمد حمزة, شذى (University of Thi-Qar Journal of Science, 2017)
This reaserch study germination for three species from Zyophyllaceae family : Fagonia bruguieri (shuika) , Peganumharmala (harmal) , Tribulus terresteris ( kutob) .The experiment condected by repeated three times and emergenc of radicale indication of germination . So two sets of seeds have used in study , one set after ripining season directly and other six month later . First stage planted in natural inviroment by soil bringing from plant, s inviroment in pots in room temperature in three times periods in January , February and April .The result: germination has failed with new ripining seeds but Peganum harmala has small percentge of germination , when the other set of seeds have succeeded germination at same three periods with different percentage  among three species . The other experiment conducted in laboratory under physical conditions to breaking dormancy of seeds . The result: three species have different ranges for germination under different inviromental conditions .